PMS2 Expression With Combination of PD-L1 and TILs for Predicting Survival of Esophageal Squamous Cell Carcinoma - Jiang, Dongxian; Song, Qi; Wei, Xiaojun; Yu, Zixiang; Liu, Yufeng; Wang, Haixing; Wang, Xingxing; Huang, Jie; Su, Jieakesu; Hong, Yang; Xu, Yifan; Xu, Chen; et al. (Frontiers in Oncology, 2022)
Background: DNA mismatch repair (MMR) deficiency (dMMR) has been recognized as an important biomarker for immunotherapy in esophageal squamous cell carcinoma (ESCC), along with programmed death ligand 1 (PD-L1) expression and/or tumor-infiltrated lymphocytes (TILs). However, in ESCC, MMR protein assessment have not been well studied at present. Methods: A total of 484 ESCC tissues treated between 2007 and 2010 in our hospital were enrolled. Immunohistochemical expression of MLH1, MSH2, MSH6, PMS2 and PD-L1 on tissue microarray specimens, and clinicopathological features, including TILs, were analyzed retrospectively. Results: Out of the 484 studied cases, loss of MLH1, MSH2, MSH6, and PMS2 expression were found in 6.8%, 2.1%, 8.7%, and 4.8% patients. dMMR was found in 65 patients, 37 cases involved in one MMR protein, 17 cases involved in two proteins, 7 cases involved in three proteins, and 4 cases involved in four proteins. There was no significant survival difference between pMMR (MMR-proficient) and dMMR patients (P>0.05). However, 224 patients with low PMS2 expression had better DFS and OS than 260 patients with high PMS2 expression (P=0.006 for DFS and 0.008 for OS), which was identified as independent prognostic factor in multivariate analyses. Positive PD-L1 expression was detected in 341 (70.5%)samples. In stage I-II disease, patients with PD-L1 expression had better DFS and OS than those withoutPD-L1 expression(P<0.05), which were not found in stage III-IV disease. With the ITWG system, 40.1% cases were classified as high TILs. Patients in the high-TILs group tended to have better DFS (P=0.055) and OS (P=0.070) than those in the low-TILs group, and the differences were statistically significant in pMMR, high MSH6 or PMS2 expression cases (P<0.05). What’s more, high PMS2 expression patients, with both PD-L1 expression and high TILs, had similar DFS and OS with low PMS2 expression patients (P>0.05), which were much better than other high PMS2 expression patients. Conclusion: The expression level of MMR proteins could also be used as prognostic factor in ESCC, and PMS2 expression outperformed other MMR protein for predicting survival. The combination of PD-L1 expression and TILs may lead to more efficient risk stratification of ESCC.